The annexation of Assam, 1824-1854 - Lahiri, Rebati Mohan (Calcutta Firma K. L. Mukhopadhyay, 1975)
Study of political history of Assam, 1824-1854.
Originally presented as the author's thesis, University of Calcutta.
Includes index.
Bibliography: p. [246]-248.
Keywords: Assam (India) -- Politics and government